Solid‐Solution Limits and Thorough Characterization of Bulk β‐(AlxGa1‐x)2O Single Crystals Grown by the Czochralski Method - Zbigniew Galazka; Andreas Fiedler; Andreas Popp; Palvan Seyidov; Saud Bin Anooz; Roberts Blukis; Jana Rehm; Kornelius Tetzner; Mike Pietsch; Andrea Dittmar; Steffen Ganschow; Arub Akhtar; et al. (Advanced Materials Interfaces)
Abstract With comprehensive crystal growth experiments of β‐(AlxGa1‐x)2O3 by the Czochralski method this work concludes a maximum [Al] = 40 mol% (35 mol% in the melt) that can be incorporated into β‐Ga2O3 crystal lattice while keeping single crystalline and monoclinic phase, resulting in the formula of β‐(Al0.4Ga0.6)2O3. Transmission Electron Microscopy (TEM) analysis reveals random distribution of Al across both octahedral and tetrahedral sites. This work has shown, that incorporation of only [Ga] ≥ 5 mol% into α‐Al2O3 crystals leads to a phase separation of (α + θ)‐Al2O3. With electrical measurements this work proves an increase of the electrical resistivity of β‐(AlxGa1‐x)2O3:Mg as compared to β‐Ga2O3:Mg. The static dielectric constant and refractive index both decrease with [Al]. Raman spectra shows a continuous shift and broadening of the peaks, with the low energy optical phonons Ag(3) having a large contribution to a decrease in the electron mobility. Further, Ir incorporation into the crystals decreases with [Al], wherein Ir4+ Raman peak disappears already at [Al] ≥ 15 mol%. Finally, thermal conductivity measurements on β‐(AlxGa1‐x)2O3 crystals show a drastic decrease of its values with [Al], to about 1/3 of the β‐Ga2O3 value at [Al] = 30 mol%.